Konsep Peran Serta Masyarakat Hukum Adat (MHA), Lokal dan Tradisional dalam Mengajukan dan Pembatalan Persetujuan Izin Kegiatan Penataan Ruang Terhadap Wilayah Pesisir dan Pulau-Pulau Kecil dalam Rezim Sentralisasi - Saeful Kholik; Maret Priyanta; Nadia Astriani (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The enactment of the UUCK has an impact on the role of customary, local and traditional law communities in the implementation of spatial planning. Especially in terms of the right to apply for and cancel the approval of permits for spatial planning activities, where the change in phrase from the cancellation of the permit to the cancellation of the approval of conformity which causes a reduction in the rights of customary law communities and conflicts between groups in maintaining and managing coastal areas and small islands in Indonesia. Based on this, the problems are identified, including: 1. What is the impact of reducing the participation of customary, local and traditional law communities in submitting demands for the cancellation of spatial planning permit approvals for coastal areas and small islands. 2. What is the concept of the participation of customary, local and traditional law communities in submitting approval for spatial planning permits for coastal areas and small islands in the centralization regime. This research method is juridical-normative, namely examining the problems of social and regulatory symptoms. The results of the study state the concept of the role of MHA in the cancellation of spatial planning permits using the Bottom-Up system. Where local governments and districts/cities are the main doors to the cancellation and application for permits for the implementation of spatial planning. In addition, the authority of local governments must be given a larger portion to accommodate suggestions and opinions from MHA on the suitability of spatial plans.